DIW economic outlook - Ferdinand Fichtner; Guido Baldi; Franziska Bremus; Karl Brenke; Christian Dreger; Hella Engerer; Christoph Große Steffen; Simon Junker; Claus Michelsen; Katharina Pijnenburg; Maximilian Podstawski; Malte Rieth; et al. (DIW Economic Bulletin, 2015)
The German economy is on track, and will likely grow by 1.8 percent this year; in the coming year, with a slight increase in dynamics, it will grow by 1.9 percent. With these figures DIW Berlin confirms its forecast from this summer. Employment growth continues; the unemployment rate will decrease this year to 6.4 percent, where it will remain in 2016. Due to the sharp drop in oil prices this year, inflation is low and stands at 0.4 percent; next year it will climb to 1.4 percent. Global economic growth is likely to experience a slight increase during the forecast period. In the industrialized countries in particular, the renewed drop in energy prices keeps inflation rates low. In addition, many countries have experienced steady improvements in labor markets. Together, these two factors support consumption and the purchasing power of households. Recovery in the euro area is moving forward. The euro's external value is low, the monetary policy is very expansionary, and major trading partners are growing vigorously; consumption is likely to develop well, and in the course of time, corporate investment is also expected to recover. In the emerging markets, growth will remain subdued this year. Higher financial market volatility is leading to deterioration in financing conditions. They are expected to contribute more to global growth next year, when for example Russia and Brazil have emerged from recession. German exports continue their upward trend: A strong upturn in major industrial countries, as well as the continued recovery within the euro area, are compensating for the somewhat weaker demand from the emerging countries. In net terms, however, foreign trade barely contributes to growth, because imports will increase significantly as part of the dynamic domestic economy. Consumption is supporting the growth of the German economy. The low inflation substantially supports consumers' purchasing power. But nominal incomes are also experiencing strong increases: The employment growth continues - the number of employed individuals is expected to rise at roughly the rate of previous quarters - and wages have noticeably increased, also due to the introduction of the minimum wage. Other important factors are the significant increases in social benefits; these are primarily due to a sharp increase in pensions, but also to the benefits being received by the refugees, which should give private consumption an additional boost. In contrast, investment will be rather subdued overall. Concerns about the future of the euro area are likely to dampen investment plans. Furthermore, considerable uncertainties about the development of important markets have recently intensified, particularly in China. There are also unresolved geopolitical conflicts, especially the tensions with Russia. Nevertheless, a moderate expansion of investment in equipment is emerging. With robust foreign demand and fully utilized capacities in the industry, these investments are expected to rise over time, especially since the dynamic domestic demand should provide an impetus. However, the risks to the economy remain high and in fact have recently increased. The impending interest rate turnaround in the U.S. could lead to unexpectedly strong capital outflows from the emerging countries; given the high private debt - especially since it is often in foreign currency - this could dampen economic momentum in these countries as well. Although a significant slump in the Chinese economy is expected to be handled with expansionary measures by the government, there is the risk that they may not take sufficient countermeasures in time. It has also been shown in the past that uncertainty about the further development of European integration can flare up quickly. In addition, the recently high volatility of oil prices shows that a new stable equilibrium still has not been established on the market. The planning uncertainty bound up with this could dampen the disposition of many corporations more strongly than assumed here.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook